PECULIARITIES OF CORROSION OF THE EQUIPMENT OF THE SYSTEM OF PURIFICATION OF HYDROCARBON GASES FROM ACIDIC COMPONENTS - Murodov Malik Negmurodovich; Rayimov Zukhriddin Khayriddin ogli (American Journals, 2023)
Today it is difficult to imagine various sectors of the national economy, including the oil and gas and chemical industries, without metal equipment. Equipment used in various industries is constantly exposed to external and internal environments, as a result of which metal equipment loses its original properties. This, in turn, leads to the formation of oxides and hydroxides of the metals used as a result of contact with the external and internal environment, and corrosion of metal equipment is observed.The article analyzes the causes of corrosion damage to metal equipment and equipment of devices for purifying hydrocarbon gases from acidic components.
Keywords: MDEA (methyldiethanolamine), corrosion, pitting, pitting, solid-uneven, shell-and-tube heat exchanger, piping network